Factors Affecting Fraudulent Financial Statements Using Fraud Triangle Analysis (Study of Manufacturing Companies Listed on the Bursa Efek Indonesia) - Annisa, Nada; Kuntadi, Cris (Universitas Dinamika, 2024)
This research aims to determine the influence of the fraud triangle on the influence of existence financial statement fraud. The factors in the fraud triangle consist of three indicators these include (1) Preasure is proxied by financial targets (ROA) and financial stability (ACchange), (2) Opportunity is proxied by Nature of Industry (Receivable) and Ineffective Monitoring (IND), (3) Rationalization is proxied by Change in auditor (CiA). There are 5 (five) independent variables that are hypothesized to influence financial statement fraud and The dependent variable fraud (F-score) is used to determine the presence of fraudulent reports finance. This research uses a quantitative approach with a sample consisting of 180 people manufacturing companies listed on the Bursa Efek Indonesiafor the observation period 2019 - 2023 using the purposive sampling method and multiple linear analysis using SPSS software version 16. The research results show that the financial stability variable (ACchange) has a positive effect, Nature of Industry (Receivable) has a negative effect, and Ineffective Monitoring (IND), has an effect negative, towards fraudulent financial statements. Meanwhile, the financial target (ROA) and variables change in auditor (CiA), has no effect on fraudulent financial statements in the company manufacturers listed on the Bursa Efek Indonesia (BEI) for the period 2019 -2023.